Stain-resistant automotive interior material and preparation method thereof
By adding modified polyacrylamide and modified polyurethane to the nonwoven base fabric of automotive interior materials, and using ultraviolet light irradiation technology, the existing materials have been solved inadequate stain resistance and photoaging problems, and the material has been achieved. Improved wear resistance and UV aging resistance.
Patent Information
- Application Number
- CN202411809815.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-07-15
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The stain resistance of existing automotive interior materials is insufficient, and performance degradation caused by photoaging is prone to occur under sunlight.
By adding modified polyacrylamide to the nonwoven base cloth raw material, modifying the polyurethane solution, and combining ultraviolet light irradiation technology, a stain-resistant automotive interior material was prepared.
It improves the stain resistance, wear resistance and UV aging resistance of automotive interior materials, and enhances the service life and performance stability of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of automobile interior decoration materials, and in particular to a stain-resistant automobile interior decoration material and a preparation method thereof. Background Art
[0002] Today, microfiber synthetic leather and natural leather are two common materials used as important materials in automotive interiors. Since natural leather is relatively expensive and its resources are relatively scarce, as a substitute for natural leather, microfiber synthetic leather not only has the advantages of high utilization rate and easy cutting, but also alleviates the shortage of genuine leather resources in my country.
[0003] At present, microfiber synthetic leather is mainly used in seats, door panels, armrests and other parts of automobile interiors. Since these parts are in contact all year round, they are extremely susceptible to various external pollution. At the same time, since automobile interiors are often exposed to sunlight, various performance degradations caused by light aging will occur. Therefore, it is urgent to improve its stain resistance and anti-ultraviolet aging performance. Summary of the invention
[0004] The purpose of the present invention is to provide a stain-resistant automobile interior material and a preparation method thereof, which solves the problem of insufficient stain resistance of existing automobile interior materials and also has good wear resistance and anti-ultraviolet aging performance.
[0005] The object of the present invention can be achieved by the following technical scheme: A stain-resistant automobile interior material is prepared by the following steps: Step S1: weighing the following raw materials in parts by weight: 60-70 parts of high shrinkage polyester, 5-10 parts of modified polyacrylamide and 20-25 parts of nylon 6; The modified polyacrylamide and nylon 6 are mixed and added to a twin-screw extruder for extrusion and melting at a melting temperature of 255°C. The high shrinkage polyester is added to another twin-screw extruder for extrusion and melting at a melting temperature of 280°C. The molten extrudate is added to a spinning manifold, extruded from a spinneret, side-blown, stretched, and spunlace. The spinning temperature is 60°C, the spinneret is a hollow orange-segment type, and the stretching pressure is 5.5 bar to obtain a nonwoven base fabric. Step S2: polyvinyl alcohol is mixed with deionized water to obtain a polyvinyl alcohol solution, the mass fraction of the polyvinyl alcohol solution is 5%, the non-woven base fabric is immersed in the polyvinyl alcohol solution, double-dipping and double-rolling, the liquid carrying rate is 60%, and drying is performed to obtain a sizing base fabric; Step S3: Weigh the following raw materials in weight percentage: 18-22% of modified polyurethane, 1-2% of N,N-dimethylacetamide, 1% of photoinitiator, and the balance of water, mix the modified polyurethane, N,N-dimethylacetamide and deionized water to prepare a modified polyurethane solution, immerse the sizing base fabric in the modified polyurethane solution, perform double dipping and double rolling, and the liquid carrying rate is 75%, then irradiate with ultraviolet light for 3-5 minutes, dry, desize, and sand, to obtain a stain-resistant automotive interior material.
[0006] The modified polyacrylamide is prepared by the following steps: Step A1: p-Hydroxybenzaldehyde, potassium carbonate and acetone are mixed, stirred at a stirring rate of 300-400 rpm and a temperature of 56° C., 3-bromopropylene is added, and the reaction is carried out for 8-10 hours to obtain intermediate 1; intermediate 1, 4-acetylbenzoic acid and ethanol are mixed, stirred at a stirring rate of 300-400 rpm and room temperature, sodium hydroxide solution is added, and the reaction is carried out for 6-8 hours to obtain intermediate 2; The dosage ratio of p-hydroxybenzaldehyde, potassium carbonate and 3-bromopropylene is 0.1-0.12 mol: 13.5-14 g: 0.1-0.12 mol, the molar concentration of the sodium hydroxide solution is 3 mol / L, and the dosage ratio of the intermediate 1,4-acetylbenzoic acid and the sodium hydroxide solution is 0.1-0.12 mol: 0.1-0.12 mol: 50-60 mL; During the reaction, the hydroxyl group in p-hydroxybenzaldehyde undergoes substitution reaction with the bromine in 3-bromopropylene to obtain intermediate 1. The aldehyde group in intermediate 1 then undergoes aldehyde-ketone condensation with the acetyl ketone group in 4-acetylbenzoic acid to form an α,β-unsaturated carbonyl group to obtain intermediate 2. Step A2: Mix intermediate 2, ethanol and propane sulfonic acid pyridinium salt, and react for 2-3 hours at a stirring rate of 300-400 rpm and a temperature of 120° C. to obtain intermediate 3; mix intermediate 3, hydroxy silicone oil, butyl phthalate, piperidinol oxide and toluene, and react for 8-10 hours at a stirring rate of 500-600 rpm and a temperature of 80° C. to obtain modified silicone oil; The ratio of intermediate 2, ethanol and propane sulfonic acid pyridinium salt is 0.1-0.12 mol: 0.12-0.14 mol: 1-2 mL, and the ratio of intermediate 3, hydroxy silicone oil, butyl phthalate and piperidinol oxide is 0.1-0.12 mol: 25-30 g: 0.5-0.8 g: 0.5 g; During the reaction, under the action of propane sulfonic acid pyridinium salt, the carboxyl group in intermediate 2 and the hydroxyl group in ethanol undergo esterification reaction to obtain intermediate 3, and then under the action of butyl phthalate and piperidinol oxide, the ester group in intermediate 3 and the hydroxyl group in hydroxy silicone oil undergo ester exchange reaction to obtain modified silicone oil; Step A3: Modified silicone oil, acrylamide, glycidyl methacrylate, propylene glycol methyl ether and deionized water are mixed, stirred at a stirring rate of 500-600 rpm and a temperature of 55° C. in a dark place, and ammonium persulfate is added and reacted for 6-8 hours to obtain modified polyacrylamide; The usage ratio of modified silicone oil, acrylamide, glycidyl methacrylate and ammonium persulfate is 25-30g: 0.2-0.24mol: 0.04-0.05mol: 0.8-1g; During the reaction, in propylene glycol methyl ether and deionized water, the modified silicone oil, acrylamide and the double bond in the middle of glycidyl methacrylate are polymerized under the action of ammonium persulfate to obtain modified polyacrylamide. The modified polyurethane is prepared by the following steps: Step B1: dodecafluoroheptyl methacrylate, γ-mercaptopropyltriethoxysilane, acrylate and tetrahydrofuran are mixed, stirred at a stirring rate of 400-500 rpm and a temperature of 70°C, and azobisisobutyronitrile is added to react for 24 hours to obtain a silane-terminated prepolymer, γ-aminopropyltriethoxysilane and an ethanol solution are mixed, and a hydrochloric acid solution is added to adjust the pH to 4, and then the reaction is carried out at a stirring rate of 400-500 rpm and a temperature of 60°C for 3-4 hours, and then the silane-terminated prepolymer is added, and the reaction is continued for 3-4 hours to obtain a modified oligosiloxane; The dosage ratio of dodecafluoroheptyl methacrylate, γ-mercaptopropyltriethoxysilane, acrylate and azobisisobutyronitrile is 0.03-0.04 mol: 0.01 mol: 0.02-0.03 mol: 0.5 g, the volume fraction of ethanol in the ethanol solution is 80%, the mass fraction of the hydrochloric acid solution is 1 mol / L, and the dosage ratio of γ-aminopropyltriethoxysilane and silane-terminated prepolymer is 0.2-0.3 mol: 10-12 g; During the reaction, under the action of azobisisobutyronitrile, the double bonds in dodecafluoroheptyl methacrylate and acrylate are polymerized, and the double bonds are terminated by the reaction with the mercapto group in γ-mercaptopropyltriethoxysilane to prepare a silane-terminated prepolymer, while the γ-aminopropyltriethoxysilane and the ethoxy group in the silane-terminated prepolymer are hydrolyzed and condensed to prepare an amino-functionalized modified oligosiloxane. Step B2: polytetramethylene glycol, isophorone diisocyanate, 2,2-bis(hydroxymethyl)propionic acid and modified oligosiloxane are mixed, and reacted for 3-4 hours at a stirring rate of 200-300 rpm and a temperature of 80° C., and then 4-hydroxychalcone is added and the reaction is continued for 4-5 hours to obtain a modified polyurethane; The dosage ratio of polytetramethylene glycol, isophorone diisocyanate, 2,2-bis(hydroxymethyl)propionic acid, modified oligosiloxane and 4-hydroxychalcone is 14-16g: 0.04-0.05mol: 0.01-0.012mol: 4-6g: 0.02-0.03mol; During the reaction, the hydroxyl groups in the polytetramethylene glycol and 2,2-bis(hydroxymethyl)propionic acid and the amino groups in the modified oligosiloxane react with the isocyanate groups in the isophorone diisocyanate to form isocyanate-terminated groups, which react with the hydroxyl groups in the added 4-hydroxychalcone to obtain a 4-hydroxychalcone-terminated modified polyurethane. Beneficial effects of the invention: The invention relates to a stain-resistant automobile interior material and a preparation method thereof. By adding modified polyacrylamide to the raw material of the non-woven base fabric used in the automobile interior material and modifying the used polyurethane solution, the problem of insufficient stain resistance of the automobile interior material is solved, and the material has good wear resistance and anti-ultraviolet aging performance; the modified polyacrylamide is added to the raw material of the non-woven base fabric, and since the modified polyacrylamide contains epoxy groups, the epoxy groups can react with nylon 6, thereby improving the compatibility of the modified polyacrylamide and nylon 6, thereby making the modified polyacrylamide play a better role, and since the silicone oil segment exists in the modified polyacrylamide, it will tend to the outside of the fiber during the melt blending preparation process, thereby exposing the α, β-unsaturated carbonyl groups contained therein, and since the modified polyacrylamide solution also contains α, β-unsaturated The modified polyacrylamide with α,β-unsaturated carbonyl groups undergoes cyclization under the conditions of photoinitiator and ultraviolet light, so that the modified polyurethane is better fixed on the non-woven base fabric, thereby reducing the performance loss caused by the shedding of polyurethane during use. At the same time, the α,β-unsaturated carbonyl group itself is also a good ultraviolet absorption group, which makes the automotive interior material have good resistance to ultraviolet aging. The modified polyurethane used in the modified polyurethane solution contains modified oligosiloxane containing perfluorinated long chains. Since the modified oligosiloxane is prepared by cross-linking with each other to form a silicon-oxygen bond structure after ethoxy hydrolysis, a form is formed in which the reactive group amino group and the chain segment containing the perfluorinated long chain are outside and the silicon-oxygen structure is inside. The existence of this structure and the change of its surface energy by the perfluorinated long chain can better improve the stain resistance of the surface of the automotive interior material. DETAILED DESCRIPTION
[0007] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0008] Example 1 A stain-resistant automotive interior material is prepared by the following steps: Step S1: Weigh the following raw materials in parts by weight: 60 parts of commercially available DN001 high shrinkage polyester, 5 parts of modified polyacrylamide and 20 parts of commercially available NC010 nylon 6, mix the modified polyacrylamide and nylon 6 and add them to a twin-screw extruder for extrusion melting, the melting temperature is 255°C, add the high shrinkage polyester to another twin-screw extruder for extrusion melting, the melting temperature is 280°C, add the molten extrudate to a spinning manifold, extrude from a spinneret, side-blown, stretched, and hydroentangled, the spinning temperature is 60°C, the spinneret is a hollow orange-segment type, and the stretching pressure is 5.5 bar, to obtain a non-woven base fabric; Step S2: PVA2488 polyvinyl alcohol is mixed with deionized water to prepare a polyvinyl alcohol solution, the mass fraction of the polyvinyl alcohol solution is 5%, the non-woven base fabric is immersed in the polyvinyl alcohol solution, double-immersed and double-rolled, the liquid carrying rate is 60%, and dried to obtain a sizing base fabric; Step S3: Weigh the following raw materials in weight percentage: 18% modified polyurethane, 1% N,N-dimethylacetamide, 1173 photoinitiator, and the balance water, mix the modified polyurethane, N,N-dimethylacetamide and deionized water to prepare a modified polyurethane solution, immerse the sizing base fabric in the modified polyurethane solution, perform double dipping and double rolling, and the liquid carrying rate is 75%, then irradiate with ultraviolet light for 3 minutes, dry, desize, and sand to obtain a stain-resistant automotive interior material.
[0009] The modified polyacrylamide is prepared by the following steps: Step A1: p-Hydroxybenzaldehyde, potassium carbonate and acetone were mixed, stirred at a stirring rate of 300 rpm and a temperature of 56°C, 3-bromopropylene was added, and the reaction was carried out for 10 hours to obtain intermediate 1; intermediate 1, 4-acetylbenzoic acid and ethanol were mixed, stirred at a stirring rate of 300 rpm and room temperature, sodium hydroxide solution was added, and the reaction was carried out for 8 hours to obtain intermediate 2; The dosage ratio of p-hydroxybenzaldehyde, potassium carbonate and 3-bromopropylene is 0.1 mol: 13.5 g: 0.1 mol, the molar concentration of the sodium hydroxide solution is 3 mol / L, and the dosage ratio of the intermediate 1,4-acetylbenzoic acid and the sodium hydroxide solution is 0.1 mol: 0.1 mol: 50 mL; Step A2: Mix intermediate 2, ethanol and propane sulfonic acid pyridinium salt, and react for 3 hours at a stirring rate of 300 rpm and a temperature of 120° C. to obtain intermediate 3; mix intermediate 3, hydroxy silicone oil, butyl phthalate, piperidinol oxide and toluene, and react for 10 hours at a stirring rate of 500 rpm and a temperature of 80° C. to obtain modified silicone oil; The ratio of intermediate 2, ethanol and propane sulfonic acid pyridinium salt is 0.1 mol: 0.12-0.14 mol: 1 mL, and the ratio of intermediate 3, hydroxy silicone oil, butyl phthalate and piperidinol oxide is 0.1 mol: 25-30 g: 0.5 g: 0.5 g; Step A3: Modified silicone oil, acrylamide, glycidyl methacrylate, propylene glycol methyl ether and deionized water were mixed, stirred at a stirring rate of 500 rpm and a temperature of 55° C. in a dark place, and ammonium persulfate was added and reacted for 8 hours to obtain modified polyacrylamide; The usage ratio of modified silicone oil, acrylamide, glycidyl methacrylate and ammonium persulfate is 25g:0.2mol:0.04mol:0.8g; The modified polyurethane is prepared by the following steps: Step B1: dodecafluoroheptyl methacrylate, γ-mercaptopropyltriethoxysilane, acrylate and tetrahydrofuran are mixed, stirred at a stirring rate of 400 rpm and a temperature of 70°C, and azobisisobutyronitrile is added to react for 24 hours to obtain a silane-terminated prepolymer, γ-aminopropyltriethoxysilane and an ethanol solution are mixed, and a hydrochloric acid solution is added to adjust the pH to 4, and then the mixture is reacted for 3-4 hours at a stirring rate of 400 rpm and a temperature of 60°C, and the silane-terminated prepolymer is added to continue the reaction for 4 hours to obtain a modified oligosiloxane; The dosage ratio of dodecafluoroheptyl methacrylate, γ-mercaptopropyltriethoxysilane, acrylate and azobisisobutyronitrile is 0.03 mol: 0.01 mol: 0.02 mol: 0.5 g, the volume fraction of ethanol in the ethanol solution is 80%, the mass fraction of the hydrochloric acid solution is 1 mol / L, and the dosage ratio of γ-aminopropyltriethoxysilane and silane-terminated prepolymer is 0.2 mol: 10 g; Step B2: polytetrahydrofuran ether diol, isophorone diisocyanate, 2,2-bis(hydroxymethyl)propionic acid and modified oligosiloxane were mixed, and the mixture was reacted for 4 hours at a stirring rate of 200 rpm and a temperature of 80° C., and 4-hydroxychalcone was added, and the reaction was continued for 5 hours to obtain a modified polyurethane; The amount ratio of polytetramethylene ether diol, isophorone diisocyanate, 2,2-bis(hydroxymethyl)propionic acid, modified oligosiloxane and 4-hydroxychalcone is 14g:0.04mol:0.01mol:4g:0.02mol.
[0010] Example 2 A stain-resistant automotive interior material is prepared by the following steps: Step S1: Weigh the following raw materials in parts by weight: 70 parts of commercially available DN001 high shrinkage polyester, 5 parts of modified polyacrylamide and 25 parts of commercially available NC010 nylon 6, mix the modified polyacrylamide and nylon 6 and add them to a twin-screw extruder for extrusion melting at a melting temperature of 255°C, add the high shrinkage polyester to another twin-screw extruder for extrusion melting at a melting temperature of 280°C, add the molten extrudate to a spinning manifold, extrude from a spinneret, side-blown, stretched, and hydroentangled, the spinning temperature is 60°C, the spinneret is a hollow orange-segment type, and the stretching pressure is 5.5 bar, to obtain a non-woven base fabric; Step S2: PVA2488 polyvinyl alcohol is mixed with deionized water to prepare a polyvinyl alcohol solution, the mass fraction of the polyvinyl alcohol solution is 5%, the non-woven base fabric is immersed in the polyvinyl alcohol solution, double-immersed and double-rolled, the liquid carrying rate is 60%, and dried to obtain a sizing base fabric; Step S3: Weigh the following raw materials in weight percentage: 18% of modified polyurethane, 2% of N,N-dimethylacetamide, 1173 photoinitiator, and the balance of water, mix the modified polyurethane, N,N-dimethylacetamide and deionized water to prepare a modified polyurethane solution, immerse the sizing base fabric in the modified polyurethane solution, perform double dipping and double rolling, and the liquid carrying rate is 75%, then irradiate with ultraviolet light for 5 minutes, dry, desize, and sand to obtain a stain-resistant automotive interior material.
[0011] The modified polyacrylamide is prepared by the following steps: Step A1: p-Hydroxybenzaldehyde, potassium carbonate and acetone were mixed, stirred at a stirring rate of 400 rpm and a temperature of 56°C, 3-bromopropylene was added, and the reaction was carried out for 8 hours to obtain intermediate 1; intermediate 1, 4-acetylbenzoic acid and ethanol were mixed, stirred at a stirring rate of 400 rpm and room temperature, sodium hydroxide solution was added, and the reaction was carried out for 6 hours to obtain intermediate 2; The dosage ratio of p-hydroxybenzaldehyde, potassium carbonate and 3-bromopropylene is 0.12 mol: 13.5 g: 0.1 mol, the molar concentration of the sodium hydroxide solution is 3 mol / L, and the dosage ratio of the intermediate 1,4-acetylbenzoic acid and the sodium hydroxide solution is 0.1 mol: 0.12 mol: 60 mL; Step A2: Mix intermediate 2, ethanol and propane sulfonic acid pyridinium salt, and react for 2 hours at a stirring rate of 400 rpm and a temperature of 120° C. to obtain intermediate 3. Mix intermediate 3, hydroxy silicone oil, butyl phthalate, piperidinol oxide and toluene, and react for 8 hours at a stirring rate of 600 rpm and a temperature of 80° C. to obtain modified silicone oil. The ratio of intermediate 2, ethanol and propane sulfonic acid pyridinium salt is 0.1 mol: 0.14 mol: 2 mL, and the ratio of intermediate 3, hydroxy silicone oil, butyl phthalate and piperidinol oxide is 0.12 mol: 25 g: 0.5 g: 0.5 g; Step A3: Modified silicone oil, acrylamide, glycidyl methacrylate, propylene glycol methyl ether and deionized water were mixed, stirred at a stirring rate of 600 rpm and a temperature of 55° C. in a dark place, and ammonium persulfate was added and reacted for 6 hours to obtain modified polyacrylamide; The usage ratio of modified silicone oil, acrylamide, glycidyl methacrylate and ammonium persulfate is 25g:0.2mol:0.05mol:0.8g; The modified polyurethane is prepared by the following steps: Step B1: dodecafluoroheptyl methacrylate, γ-mercaptopropyltriethoxysilane, acrylate and tetrahydrofuran are mixed, stirred at a stirring rate of 500 rpm and a temperature of 70°C, and azobisisobutyronitrile is added to react for 24 hours to obtain a silane-terminated prepolymer, γ-aminopropyltriethoxysilane and an ethanol solution are mixed, and a hydrochloric acid solution is added to adjust the pH to 4, and then the mixture is reacted for 3 hours at a stirring rate of 500 rpm and a temperature of 60°C, and the silane-terminated prepolymer is added and the reaction is continued for 3 hours to obtain a modified oligosiloxane; The dosage ratio of dodecafluoroheptyl methacrylate, γ-mercaptopropyltriethoxysilane, acrylate and azobisisobutyronitrile is 0.04 mol: 0.01 mol: 0.02 mol: 0.5 g, the volume fraction of ethanol in the ethanol solution is 80%, the mass fraction of the hydrochloric acid solution is 1 mol / L, and the dosage ratio of γ-aminopropyltriethoxysilane and silane-terminated prepolymer is 0.2 mol: 10 g; Step B2: polytetrahydrofuran ether diol, isophorone diisocyanate, 2,2-bis(hydroxymethyl)propionic acid and modified oligosiloxane were mixed, and the mixture was reacted for 3 hours at a stirring rate of 300 rpm and a temperature of 80° C., and then 4-hydroxychalcone was added and the reaction was continued for 4 hours to obtain a modified polyurethane; The amount ratio of polytetramethylene ether diol, isophorone diisocyanate, 2,2-bis(hydroxymethyl)propionic acid, modified oligosiloxane and 4-hydroxychalcone is 14g:0.04mol:0.01mol:6g:0.02mol.
[0012] Example 3 A stain-resistant automotive interior material is prepared by the following steps: Step S1: Weigh the following raw materials in parts by weight: 70 parts of commercially available DN001 high shrinkage polyester, 10 parts of modified polyacrylamide and 25 parts of commercially available NC010 nylon 6, mix the modified polyacrylamide and nylon 6 and add them to a twin-screw extruder for extrusion melting at a melting temperature of 255°C, add the high shrinkage polyester to another twin-screw extruder for extrusion melting at a melting temperature of 280°C, add the molten extrudate to a spinning manifold, extrude from a spinneret, side-blown, stretched, and hydroentangled, the spinning temperature is 60°C, the spinneret is a hollow orange-segment type, and the stretching pressure is 5.5 bar, to obtain a non-woven base fabric; Step S2: PVA2488 polyvinyl alcohol is mixed with deionized water to prepare a polyvinyl alcohol solution, the mass fraction of the polyvinyl alcohol solution is 5%, the non-woven base fabric is immersed in the polyvinyl alcohol solution, double-immersed and double-rolled, the liquid carrying rate is 60%, and dried to obtain a sizing base fabric; Step S3: Weigh the following raw materials in weight percentage: 22% of modified polyurethane, 2% of N,N-dimethylacetamide, 1173 photoinitiator, and the balance of water, mix the modified polyurethane, N,N-dimethylacetamide and deionized water to prepare a modified polyurethane solution, immerse the sizing base fabric in the modified polyurethane solution, perform double dipping and double rolling, and the liquid carrying rate is 75%, then irradiate with ultraviolet light for 5 minutes, dry, desize, and sand to obtain a stain-resistant automotive interior material.
[0013] The modified polyacrylamide is prepared by the following steps: Step A1: p-Hydroxybenzaldehyde, potassium carbonate and acetone were mixed, stirred at a stirring rate of 400 rpm and a temperature of 56°C, 3-bromopropylene was added, and the reaction was carried out for 10 hours to obtain intermediate 1; intermediate 1, 4-acetylbenzoic acid and ethanol were mixed, stirred at a stirring rate of 400 rpm and room temperature, sodium hydroxide solution was added, and the reaction was carried out for 6-8 hours to obtain intermediate 2; The dosage ratio of p-hydroxybenzaldehyde, potassium carbonate and 3-bromopropylene is 0.12 mol: 14 g: 0.12 mol, the molar concentration of the sodium hydroxide solution is 3 mol / L, and the dosage ratio of the intermediate 1, 4-acetylbenzoic acid and the sodium hydroxide solution is 0.12 mol: 0.12 mol: 60 mL; Step A2: Mix intermediate 2, ethanol and propane sulfonic acid pyridinium salt, and react for 3 hours at a stirring rate of 400 rpm and a temperature of 120° C. to obtain intermediate 3; mix intermediate 3, hydroxy silicone oil, butyl phthalate, piperidinol oxide and toluene, and react for 10 hours at a stirring rate of 600 rpm and a temperature of 80° C. to obtain modified silicone oil; The ratio of intermediate 2, ethanol and propane sulfonic acid pyridinium salt is 0.12 mol: 0.14 mol: 2 mL, and the ratio of intermediate 3, hydroxy silicone oil, butyl phthalate and piperidinol oxide is 0.12 mol: 30 g: 0.8 g: 0.5 g; Step A3: Modified silicone oil, acrylamide, glycidyl methacrylate, propylene glycol methyl ether and deionized water were mixed, stirred at a stirring rate of 600 rpm and a temperature of 55° C. in a dark place, and ammonium persulfate was added and reacted for 8 hours to obtain modified polyacrylamide; The usage ratio of modified silicone oil, acrylamide, glycidyl methacrylate and ammonium persulfate is 30g:0.24mol:0.05mol:1g; The modified polyurethane is prepared by the following steps: Step B1: dodecafluoroheptyl methacrylate, γ-mercaptopropyltriethoxysilane, acrylate and tetrahydrofuran are mixed, stirred at a stirring rate of 500 rpm and a temperature of 70°C, and azobisisobutyronitrile is added to react for 24 hours to obtain a silane-terminated prepolymer, γ-aminopropyltriethoxysilane and an ethanol solution are mixed, and a hydrochloric acid solution is added to adjust the pH to 4, and then the mixture is reacted for 4 hours at a stirring rate of 500 rpm and a temperature of 60°C, and the silane-terminated prepolymer is added and the reaction is continued for 4 hours to obtain a modified oligosiloxane; The dosage ratio of dodecafluoroheptyl methacrylate, γ-mercaptopropyltriethoxysilane, acrylate and azobisisobutyronitrile is 0.04 mol: 0.01 mol: 0.03 mol: 0.5 g, the volume fraction of ethanol in the ethanol solution is 80%, the mass fraction of the hydrochloric acid solution is 1 mol / L, and the dosage ratio of γ-aminopropyltriethoxysilane and silane-terminated prepolymer is 0.3 mol: 12 g; Step B2: polytetramethylene glycol, isophorone diisocyanate, 2,2-bis(hydroxymethyl)propionic acid and modified oligosiloxane were mixed, and the mixture was reacted for 4 hours at a stirring rate of 300 rpm and a temperature of 80° C., and then 4-hydroxychalcone was added and the reaction was continued for 5 hours to obtain a modified polyurethane; The amount ratio of polytetramethylene ether diol, isophorone diisocyanate, 2,2-bis(hydroxymethyl)propionic acid, modified oligosiloxane and 4-hydroxychalcone is 16g:0.05mol:0.012mol:6g:0.03mol.
[0014] Comparative Example 1 Compared with Example 3, this comparative example removes the ultraviolet light irradiation process in the preparation process of the stain-resistant automobile interior material in Example 3, and the other steps are the same.
[0015] Comparative Example 2 Compared with Example 3, this comparative example is different in that the glycidyl methacrylate in the preparation process of the modified polyacrylamide in Example 3 is replaced by acrylamide, and the other steps are the same.
[0016] Comparative Example 3 Compared with Example 3, this comparative example is different in that dodecafluoroheptyl methacrylate in the preparation process of the modified polyurethane in Example 3 is replaced by acrylate, and the other steps are the same.
[0017] Comparative Example 4 Compared with Example 3, this comparative example is different in that the modified oligosiloxane in the preparation process of the modified polyurethane in Example 3 is replaced by a silane-terminated prepolymer, and the other steps are the same.
[0018] Take a kind of stain-resistant automobile interior material prepared by Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, cut the stain-resistant automobile interior material into 10cm×5cm samples, use a paintbrush to dip P09PM lipstick to apply a 5cm long straight line on the surface of the sample, use a commercially available Morning Light 0.7mm ballpoint pen, and draw a 5cm long straight line on the surface of the sample with the same force, apply Heinz ketchup on the surface of the sample with a diameter of 3cm, drop commercially available Coca-Cola on the surface of the sample with a volume of 5mL, then place the above samples at a temperature of 40°C and a humidity of 95% for 24h, wipe the surface with a white wet cloth, observe the residual pollutants on the surface of the sample to evaluate its stain resistance, among which level 1 means that the tested pollutants are almost not removed, level 2 means that the tested pollutants are slightly removed, and most of the pollutants are still there, level 3 means that the tested pollutants are removed by more than 50%, level 4 means that most of the tested pollutants are removed, and level 5 means that the tested pollutants are removed. The pollutants tested are completely removed; the wear resistance is tested according to QB / T2726-2005, the grinding wheel head model is H-18, the load is 1000g, and it is observed every 50 turns, and the number of circles when the surface breaks is recorded to evaluate its wear resistance; the sample is placed in a dry sealed bag and placed in an outdoor environment with direct sunlight for 720 hours, and then its wear resistance is tested to evaluate its anti-ultraviolet aging performance. The test results are as follows:
[0019] It can be seen from the test results in the table shown that when Example 7, Example 8 and Example 9 are compared with Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, Comparative Example 1 removes the ultraviolet irradiation process in the preparation process of the stain-resistant automotive interior material in Example 3, so there is no covalent bond between the modified polyurethane and the non-woven base fabric, which leads to a decrease in its wear resistance. In Comparative Example 2, the glycidyl methacrylate in the preparation process of the modified polyacrylamide in Example 3 is replaced by acrylamide. Due to the lack of epoxy groups, its wear resistance is greatly reduced. In Comparative Example 3, dodecafluoroheptyl methacrylate in the preparation process of the modified polyurethane in Example 3 is replaced by acrylate. Due to the lack of perfluoro long chains, its stain resistance is greatly reduced. In Comparative Example 4, the modified oligosiloxane in the preparation process of the modified polyurethane in Example 3 is replaced by a silane-terminated prepolymer. Due to the lack of oligomeric structure, its stain resistance is reduced.
[0020] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a stain-resistant automobile interior material, characterized in that: The method comprises the following steps: Step S1: weighing the following raw materials in parts by weight: 60-70 parts of high shrinkage polyester, 5-10 parts of modified polyacrylamide and 20-25 parts of nylon 6; The modified polyacrylamide is prepared by the following steps: Step A1: p-Hydroxybenzaldehyde, potassium carbonate and acetone are mixed, stirred at a stirring rate of 300-400 rpm and a temperature of 56° C., 3-bromopropylene is added, and the reaction is carried out for 8-10 hours to obtain intermediate 1; intermediate 1, 4-acetylbenzoic acid and ethanol are mixed, stirred at a stirring rate of 300-400 rpm and room temperature, sodium hydroxide solution is added, and the reaction is carried out for 6-8 hours to obtain intermediate 2; Step A2: Mix intermediate 2, ethanol and propane sulfonic acid pyridinium salt, and react for 2-3 hours at a stirring rate of 300-400 rpm and a temperature of 120° C. to obtain intermediate 3; mix intermediate 3, hydroxy silicone oil, butyl phthalate, piperidinol oxide and toluene, and react for 8-10 hours at a stirring rate of 500-600 rpm and a temperature of 80° C. to obtain modified silicone oil; Step A3: Modified silicone oil, acrylamide, glycidyl methacrylate, propylene glycol methyl ether and deionized water were mixed, stirred at a stirring rate of 500-600 rpm and a temperature of 55° C. in a dark place, and ammonium persulfate was added and reacted for 6-8 hours to obtain modified polyacrylamide.
2. The method for preparing a stain-resistant automobile interior material according to claim 1, characterized in that: In step A1, the ratio of p-hydroxybenzaldehyde, potassium carbonate and 3-bromopropylene is 0.1-0.12 mol: 13.5-14 g: 0.1-0.12 mol, the molar concentration of the sodium hydroxide solution is 3 mol / L, and the ratio of the intermediate 1,4-acetylbenzoic acid and the sodium hydroxide solution is 0.1-0.12 mol: 0.1-0.12 mol: 50-60 mL.
3. The method for preparing a stain-resistant automobile interior material according to claim 1, characterized in that: In step A2, the ratio of intermediate 2, ethanol and propane sulfonic acid pyridinium salt is 0.1-0.12 mol: 0.12-0.14 mol: 1-2 mL, and the ratio of intermediate 3, hydroxy silicone oil, butyl phthalate and piperidinol oxide is 0.1-0.12 mol: 25-30 g: 0.5-0.8 g: 0.5 g.
4. The method for preparing a stain-resistant automobile interior material according to claim 1, characterized in that: In step A3: the usage ratio of modified silicone oil, acrylamide, glycidyl methacrylate and ammonium persulfate is 25-30 g: 0.2-0.24 mol: 0.04-0.05 mol: 0.8-1 g.
5. The method for preparing a stain-resistant automobile interior material according to claim 1, characterized in that: In step S1, modified polyacrylamide and nylon 6 are mixed and added to a twin-screw extruder for extrusion and melting at a melting temperature of 255°C, high shrinkage polyester is added to another twin-screw extruder for extrusion and melting at a melting temperature of 280°C, the molten extrudate is added to a spinning manifold, extruded from a spinneret, side-blown, stretched, and hydroentangled, the spinning temperature is 60°C, the spinneret is a hollow orange segment type, and the stretching pressure is 5.5 bar, to obtain a nonwoven base fabric; The preparation method further comprises the following steps: Step S2: polyvinyl alcohol is mixed with deionized water to obtain a polyvinyl alcohol solution, the mass fraction of the polyvinyl alcohol solution is 5%, the non-woven base fabric is immersed in the polyvinyl alcohol solution, double-dipping and double-rolling, the liquid carrying rate is 60%, and drying is performed to obtain a sizing base fabric; Step S3: Weigh the following raw materials in weight percentage: 18-22% of modified polyurethane, 1-2% of N,N-dimethylacetamide, 1% of photoinitiator, and the balance of water, mix the modified polyurethane, N,N-dimethylacetamide and deionized water to prepare a modified polyurethane solution, immerse the sizing base fabric in the modified polyurethane solution, perform double dipping and double rolling, and the liquid carrying rate is 75%, then irradiate with ultraviolet light for 3-5 minutes, dry, desize, and sand, to obtain a stain-resistant automotive interior material.
6. The method for preparing a stain-resistant automobile interior material according to claim 5, characterized in that: The modified polyurethane is prepared by the following steps: Step B1: dodecafluoroheptyl methacrylate, γ-mercaptopropyltriethoxysilane, acrylate and tetrahydrofuran are mixed, stirred at a stirring rate of 400-500 rpm and a temperature of 70°C, and azobisisobutyronitrile is added to react for 24 hours to obtain a silane-terminated prepolymer, γ-aminopropyltriethoxysilane and an ethanol solution are mixed, and a hydrochloric acid solution is added to adjust the pH to 4, and then the reaction is carried out at a stirring rate of 400-500 rpm and a temperature of 60°C for 3-4 hours, and then the silane-terminated prepolymer is added, and the reaction is continued for 3-4 hours to obtain a modified oligosiloxane; Step B2: polytetramethylene glycol, isophorone diisocyanate, 2,2-bis(hydroxymethyl)propionic acid and modified oligosiloxane are mixed, and reacted for 3-4 hours at a stirring rate of 200-300 rpm and a temperature of 80°C, and then 4-hydroxychalcone is added and the reaction is continued for 4-5 hours to obtain a modified polyurethane.
7. The method for preparing a stain-resistant automobile interior material according to claim 6, characterized in that: In step B1: the amount ratio of dodecafluoroheptyl methacrylate, γ-mercaptopropyltriethoxysilane, acrylate and azobisisobutyronitrile is 0.03-0.04 mol: 0.01 mol: 0.02-0.03 mol: 0.5 g, the volume fraction of ethanol in the ethanol solution is 80%, the mass fraction of the hydrochloric acid solution is 1 mol / L, and the amount ratio of γ-aminopropyltriethoxysilane and silane-terminated prepolymer is 0.2-0.3 mol: 10-12 g.
8. The method for preparing a stain-resistant automobile interior material according to claim 6, characterized in that: In step B2, the amount ratio of polytetramethylene glycol, isophorone diisocyanate, 2,2-bis(hydroxymethyl)propionic acid, modified oligosiloxane and 4-hydroxychalcone is 14-16 g: 0.04-0.05 mol: 0.01-0.012 mol: 4-6 g: 0.02-0.03 mol.
9. A stain-resistant automotive interior material, characterized in that: Prepared according to any one of the preparation methods described in claims 1-8.
Citation Information
Patent Citations
Terminal / side fluoroalkyl co-modified polyurethane nano hybrid emulsion and preparation method thereof
CN110734533A
Corrosion-resistant bristle material and preparation method thereof
CN118307954A
Solvent-free polyurethane resin for high-flame-retardancy automobile leather, and preparation method therefor
WO2022147914A1